Designing Ubiquitous Information Environments: Socio-Technical Issues and Challenges IFIP TC8 WG 8.2 International Working Conference, August 1-3, 2005, Cleveland, Ohio, U.S.A. - Sørensen, Carsten.; Sørensen, Carsten.; Yoo, Youngjin.; Yoo, Youngjin.; Lyytinen, Kalle.; Lyytinen, Kalle.; DeGross, Janice I.; DeGross, Janice I. (IFIP Advances in Information and Communication Technology,, 2005)
The rapid developments in mobile and wireless communication technologies and the continuing miniaturization of computing devices makes ubiquitous information environments more of a technical reality than a distant vision. Ubiquituous computing as the next wave of organizational computing offers new possibilities and opportunities for organizations to improve their productivity and effectiveness. However, the emergence of ubiquitous information environments not only signals opportunities, but also fundamentally challenges many of the traditional assumptions about organizations, management, computing, communication and work. The ubiquitous information environments affect all levels of organization activities. Currently there are a number of activities in designing and implementing ubiquitous information environments. The 7 parts of this book, and the 31 chapters, cover various issues related to the design and implementation of ubiquitous information environments. The book covers old and familiar issues in light of emerging ubiquitous information environments as well as novel social and technical problems. The book brings in diverse perspectives on ubiquitous information environments, from computer-supported collaborative work, institutional perspective, diffusion of innovation, management, sociology, individual cognition, and software engineering. It also covers a variety of technologies that make up ubiquitous information environments including RFID, wireless grid, GPS, mobile phones, and wireless local area network. The papers cover many contexts of ubiquitous computing including personal use, library, automobile, healthcare, police, professional knowledge work, remote diagnostics of machines, and marketing, attesting to the wide range of potential of ubiquitous information environments. This book developed as a collective product of the International Federation for Information Processing (IFIP) Working Group 8.2, a working group dedicated to the study of the interaction of information systems and the organization. The book proceeds from the IFIP Working Conference on the Design of Ubiquitous Information Environments held in Cleveland, Ohio, in August 2005.